2020
DOI: 10.2147/dmso.s243170
|View full text |Cite
|
Sign up to set email alerts
|

<p>Empagliflozin Protects Against Proximal Renal Tubular Cell Injury Induced by High Glucose via Regulation of Hypoxia-Inducible Factor 1-Alpha</p>

Abstract: Background: Evidence from both animal and human studies clearly supports the renal beneficial effects of empagliflozin (emp), a sodium glucose co-transporter 2 (SGLT2) inhibitor, but the mechanism in which it exerts its effect is not well understood. In this study, we investigated the capability of emp on reducing hyperglycemia-induced renal proximal tubular epithelial cells injury and we evaluated if the renoprotective effect of emp associates with hypoxia-inducible factor-1α (HIF-1α). Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Tumor cells may produce reactive oxygen species (ROS), and these activate hypoxia-inducible factor 1 alpha (HIF-1a), nuclear factor kappa-B (NFkB), and consequent lactate production in the adjacent fibroblasts, which in turn is associated with faster growth of the cancer cells (40). SGLT2i has been shown to lead to a lower activity of HIF-1a in the kidneys (41)(42)(43). Data regarding the kidneys suggest that hyperglycemia may lead to an abnormal metabolism with high hexokinase and pyruvate kinase M2 activity, low Sirtuin-3 levels, an activated STAT3, and HIF1a signaling and an aberrant glycolysis similar to the Warburg effect in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells may produce reactive oxygen species (ROS), and these activate hypoxia-inducible factor 1 alpha (HIF-1a), nuclear factor kappa-B (NFkB), and consequent lactate production in the adjacent fibroblasts, which in turn is associated with faster growth of the cancer cells (40). SGLT2i has been shown to lead to a lower activity of HIF-1a in the kidneys (41)(42)(43). Data regarding the kidneys suggest that hyperglycemia may lead to an abnormal metabolism with high hexokinase and pyruvate kinase M2 activity, low Sirtuin-3 levels, an activated STAT3, and HIF1a signaling and an aberrant glycolysis similar to the Warburg effect in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway enrichment analysis identified that the acetylated proteins identified in our study were localized in a variety of pathways, including TCA cycle, amino acid metabolism, and the HIF-1α pathway. With a wide range of target genes, hypoxia-inducible factor-1 alpha (HIF-1α) has been demonstrated to be involved in EMT under high glucose conditions in renal tubular epithelial cells ( Ndibalema et al, 2020 ). It has been reported that the CREB Binding Protein (CREBBP, P300/CBP, HG/NG: 1.458 fold at K1584, 1.372 fold at K1807) is a common acetyltransferase that can bind to HIF-1α and initiates hypoxia ( Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, HIF-1α, TGF-β1, p-SMAD were suggested as regulators of SGLT2. 11) 12) 13) We did additional western blot analyses to confirm the regulation pathway of SGLT2 ( Figure 4C ). The EMPA pre-treated group showed reduced HIF-1α and TGF-β1 expression especially at 72 hr after MI.…”
Section: Resultsmentioning
confidence: 99%
“… 13) In the hypoxic conditions, HIF-1α was also reported as a regulator of SGLT2, although there are conflicting results whether HIF-1α upregulates. 11) or downregulates SGLT2. 12) We subsequently performed a western blot analysis on such proteins ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%